Research and development of silvopastoral systems in a village in the buffer zone of the El Ocote Biosphere Reserve, Chiapas, Mexico - Nahed Toral, J. (2015)
A participatory research and development project in establishment of agrosilvopastoral systems was documented. This study was carried out in the village Tierra Nueva (TN), located in the Buffer zone of the ElOcote Biosphere Reserve (EOBIRE) in the state of Chiapas, Mexico. This zone is part of the area of influence of the Mesoamerican Biological Corridor in Mexico (MBCM). A variety of methods related to agroforestry were used, along with the Farmer Field Schools Methodology by which producers may develop new aptitudes and Knowledge regarding cattle raising and conservation. The bovine production suystem and productive diversification of cattle raising units were analyzed. Grazing units are characterized and their carrying capacity estimated. Chemical - nutritional composition and ruminal degradation of foliage is characterized for woody fodder species. Finally, the experience is projected to the future in order to strengthen local innovation processes.